Long noncoding RNAs in renal diseases - Minghui Liu; Jie Ren (ExRNA)
Abstract Long noncoding RNAs (lncRNAs) play critical roles in eukaryotic gene regulation and diseases, rather than being merely transcriptional “noise”. Over the past decade, the study of lncRNAs has emerged as a burgeoning field of research and expanded our knowledge of their functions and underlining mechanisms in both normal and malignant cells. However, lncRNAs are still one of the least understood groups of transcripts. Here, we review the classifications and functions of lncRNAs and their roles in renal diseases. This review will provide insights into the roles of lncRNAs in pathogenesis, diagnosis and therapeutics of renal diseases and indications of lncRNAs as potential targets for the treatment of kidney diseases.